Proof‐of‐concept modular fluid handling prototype integrated with microfluidic biochemical assay modules for point‐of‐care testing. Issue 1 (23rd March 2020) - Sathish, Shivani; Toda‐Peters, Kazumi; Shen, Amy Q.
Abstract: Large populations around the world suffer from numerous but treatable health issues, caused by either lifestyle choices or environmental factors. Over the past decades, point‐of‐care testing kits have been developed to circumvent the reliance on laboratories, by allowing users to perform preliminary health or environmental testing from the privacy of their homes. However, these kits heavily rely on the precision of the user to perform the procedures, leading to increased variability in final assessments. To eliminate user‐induced errors, we present an integrated, completely sealed, and disposable point‐of‐care testing prototype that exploits the benefits of microfluidics and 3D‐printing fabrication techniques. The palm‐sized modular prototype consists of a manually operated fluid handling device that allows precise mixing, filtration, and delivery of fluids to an on‐board microfluidic assay unit for subsequent detection of specific biochemical analytes, with a minimized risk of contamination. Abstract : The palm‐sized device is an integrated, completely sealed, and disposable point‐of‐care testing prototype that exploits the benefits of microfluidics and 3D‐printing fabrication techniques. It consists of a manually operated fluid handling device that allows precise mixing, filtration, and delivery of fluids to an on‐board microfluidic assay unit for subsequent detection of specific biochemical analytes, with minimal risks of contamination.